Endoparasites with Zoonotic Potential in Domesticated Dogs - Bresciani, Katia Denise Saraiva; Coelho, Willian Marinho Dourado; Gomes, Jancarlo Ferreira; Apolinário, Juliana de Carvalho; Coelho, Natalia Marinho Dourado; Viol, Milena Araúz; Costa, Alvimar José da (IntechOpen, 2012)
None